2003
DOI: 10.1046/j.1471-4159.2003.02111.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective prion protein binding to synaptic components is modulated by oxidative and nitrosative changes induced by copper(II) and peroxynitrite in cholinergic synaptosomes, unveiling a role for calcineurin B and thioredoxin

Abstract: Choline acetyltransferase (ChAT) and choline transport are decreased after nitrosative stress. ChAT activity is altered in scrapie-infected neurons, where oxidative stress develops.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 87 publications
(167 reference statements)
0
8
0
Order By: Relevance
“…Repeated published reports noted that copper may play a significant role in the conversion of PrP C to PrP Sc [6][7][8][9] (Fig. 2).…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Repeated published reports noted that copper may play a significant role in the conversion of PrP C to PrP Sc [6][7][8][9] (Fig. 2).…”
Section: Introductionmentioning
confidence: 60%
“…2 ). Moreover, several reports have shown that cellular prion protein (PrP) may play a crucial role in the redox control of the neuronal environment and in the regulation of copper metabolism in a manner that contributes to disease pathology [ 7 , 10 12 ]. The concentration of copper in humans varies in different organs.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium ion flux, as well as cytoplasmic ROS, has the potential to influence the mitochondrial retrograde signaling response (reviewed by Butow and Avadhani). 123 In addition, PrP C has been linked to both protein complex 14-3-3 100 and calcineurin B, 83 both of which are known to directly affect the regulation of the K + leak channel K2P, TRESK, which determines resting membrane excitability 124 and is the only K2P channel upregulated by a Ca 2+ -dependant pathway. This may give PrP C an indirect role in this ion channel and therefore cellular electrical excitability.…”
Section: Prpmentioning
confidence: 99%
“…82 This may be linked to an interaction with the calcineurin complex. 83 PrP C has been shown to bind to many molecules, including:…”
Section: Signal Transductionmentioning
confidence: 99%
See 1 more Smart Citation